Sustainable development goals in Kazakhstan’s academic landscape: a critical bibliometric study on sustainable development - Meidutė-Kavaliauskienė, Ieva; Abdurakhmanova, Assem; Cigdem, Semsettin; Činčikaitė, Renata (Business, Management and Economics Engineering, 2024)
Purpose – The purpose of this study is to conduct a bibliometric analysis of the academic activities of Kazakhstan’s academics and to present a comprehensive map of the academic landscape in the country. Research methodology – The study combines synthesis and comparative scientific analysis of concepts and methods in the literature. It involves secondary data analysis, statistical processing, and bibliometric analysis to gather and interpret the data. Findings – The analysis reveals a significant gap between the practical applications of Sustainable Development Goals (SDGs) in Kazakhstan and the academic research on the topic. Furthermore, academic activities and practices in Kazakhstan do not align well with the official reports on the SDGs. While some SDGs have comparable publications in Kazakhstan to global averages, others present distinct challenges and problematic issues unique to the country. Research limitations – The study faces limitations due to the lack of data or difficulty accessing relevant information. Practical implications – This research is crucial for promoting SDGs as it aids in understanding global issues, identifying knowledge gaps, and fostering interdisciplinary collaboration to ad- dress complex issues related to sustainable development. Additionally, examining a country’s academic activities through the lens of SDGs is essential for assessing the nation’s academic awareness and engagement with these global goals. Originality/Value – The article provides a unique and valuable perspective on integrating sustainable development goals within Kazakhstan’s academic landscape, highlighting achievements and areas needing improvement.